Biochemical evidence of a possible new species of Neoplecostomus (Teleostei : Loricariidae) from the upper Rio Parana basin, Brazil - Zawadzki, C. H.; Alves, A. L.; Renesto, E.; Oliveira, C. (Elsevier B.V., 2004)
Neoplecostomus paranensis Langeam, 1990, from the upper Rio Parana, is the only Neoplecostomus species described in this basin and is distinguished from its congeners by the lack or reduction of the adipose fin. Neoplecostomus specimens with a normal and always present adipose fin were caught in the Rio Corumba, upper Rio Parana basin. In the present study two samples of populations, one from a tributary of Rio Paranapanema (identified as a typical N. paranensis) and the other from the Rio Corumba were compared through allozyme electrophoresis. Six diagnostic loci were found, Acp-A, Adh-A, Est-A, Gpi-A, Ldh-A and Ldh-B. In addition, the locus Gpi-B showed significant differences between allelic frequencies for the two samples. Nei's genetic identity between the populations was 0.731. The expressive genetic divergence together with the presence of an adipose fin show that the sample from the Rio Corumba is distinct from N. paranensis and probably represents a new species. (C) 2003 Published by Elsevier Ltd.
Keywords: Loricariidae; Neoplecostomus; systematic; allozymes; heterozygosity; genetic diversity; taxonomy